Patterns of thyroid hormone receptor expression in zebrafish and generation of a novel model of resistance to thyroid hormone action. (15th March 2016) - Marelli, Federica; Carra, Silvia; Agostini, Maura; Cotelli, Franco; Peeters, Robin; Chatterjee, Krishna; Persani, Luca
Abstract: Resistance to thyroid hormone can be due to heterozygous, dominant negative (DN) THRA (RTHα) or THRB (RTHβ) mutations, but the underlying mechanisms are incompletely understood. Here, we delineate the spatiotemporal expression of TH receptors (TRs) in zebrafish and generated morphants expressing equivalent amounts of wild-type and DN TRαs ( thraa _MOs) and TRβs ( thrb _MOs) in vivo . Both morphants show severe developmental abnormalities. The phenotype of thraa _MOs includes brain and cardiac defects, but normal thyroid volume and tshba expression. A combined modification of dio2 and dio3 expression can explain the high T3/T4 ratio seen in thraa _MOs, as in RTHα. Thrb _MOs show abnormal eyes and otoliths, with a typical RTHβ pattern of thyroid axis. The coexpression of wild-type, but not mutant, human TRs can rescue the phenotype in both morphants. High T3 doses can partially revert the dominant negative action of mutant TRs in morphant fish. Therefore, our morphants recapitulate the RTHα and RTHβ key manifestations representing new models in which the functional consequences of human TR mutations can be rapidly and faithfully evaluated. Highlights: We characterize the expression of TRs in zebrafish embryos and adult tissues. TR-morphants recapitulate the clinical features of RTHα or RTHβ patients. Changes in the expression of deiodinases can explain the high T3/T4 ratio of RTHα. Zebrafish and human TRs are functionally interchangeable. Mutant hTRs can variably rescue the morphant phenotypes only after high T3 doses.